Perceptions of University of Limpopo 3rd year psychology students on the inclusion of men in gender-based violence prevention campaigns in South Africa - Maboga, Vhonani Ishmael (My University, 2022)
Gender-based violence (GBV) has become a global epidemic and it affects those who are most vulnerable in society, predominantly women and children. Several causal factors have been identified, which include gender norms, socioeconomic inequalities, and South Africa’s violent history. There are many organisations (governmental and non-governmental) that are committed to reducing GBV. However, even with many interventions in place, the prevalence of GBV in South Africa keeps on rising. A qualitative approach was adopted to explore the perceptions of 3rd year psychology students at the University of Limpopo regarding the inclusion of men in GBV prevention campaigns. The study used two theoretical frameworks, namely, Social Learning Theory and Feminist Theory. Purposive sampling was used to draw a sample of 16 students (10 females, and 6 males), and the data was analysed using a Thematic Analysis (TA) approach. Three major themes and five subthemes emerged from the analysis, which was supported by existing findings. The themes were identified as GBV prevention campaigns, GBV and government interventions, and GBV knowledge and perceptions. The results of the study found that students had an adequate understanding of GBV prevention campaigns. Their understanding informed their perceptions, which leaned towards supporting the inclusion of men in GBV prevention campaigns. Their perceptions were geared towards a multi-gender approach aimed at increasing awareness, protecting the rights of GBV victims and demanding justice for them. Furthermore, a multi-gender approach was seen as a silver bullet to championing the fight against GBV and stressing the impact that the inclusion of men will have in lowering GBV cases. The current GBV prevention campaigns (both at government and non-governmental levels) were seen as not effective enough in the eradication of GBV. Therefore, a call for a multi-gender approach to GBV prevention campaigns at all societal levels was emphasised. Community-based initiatives (i.e., social organisations) in GBV prevention campaigns were also seen as crucial in the eradication of GBV.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2022
Keywords: Psychology students; Anti-rape movement; Abused children; Abused men; Abused women; Abused parents; Victims of dating violence; Victims of family violence; Psychology students; Victims of dating violence; Victims of family violence; Gender-based violence; Intimate partner violence; Family violence; College students -- South Africa -- Psychology